The Effects of Activated Carbon and Bentonite on Physicochemical Characterization of Red Fruit Oil (Pandanus conoideus Lam) - Mustika Erlinaningrum; Abdul Rohman; Agustina Ari Murti Budi Hastuti (Integrated Research and Testing Laboratory (LPPT) Universitas Gadjah Mada, 2024)
This research aims to see the quality of red fruit oil (RFO) before and after being treated with activated carbon and bentonite. The quality of red fruit oil can be seen from the analysis of physicochemical characterization determination, which includes the determination of acid value (AV), peroxide value (PV), saponification value (SV), iodine value (IV), and p-anisidine value (PAV). In this study, AV RFO ranged from 9,22-10,23 mg KOH/g, PV RFO ranged from 5,57-7,56 meq/kg, SV RFO ranged from 96,57-110,24 mgKOH/g, IV RFO ranged from 70,00-70,83 gI2/100g, and PAV RFO ranged from 5,97-7,00 meq/kg. The purification of RFO using activated carbon and bentonite significantly (p<0,05) affected the physicochemical characteristics of the oil, where the process succeeded in improving the quality of RFO by reducing acid value, peroxide value, saponification value, and p-anisidine value and increasing iodine value.